European Formation Damage Conference 2007
DOI: 10.2118/107718-ms
|View full text |Cite
|
Sign up to set email alerts
|

Single Point of Initiation, Dual-Fracture Placement for Maximizing Well Production

Abstract: fax 01-972-952-9435. AbstractPlacement of a fracture in a formation has become a wellunderstood process in the industry. Recently, this practice was improved by the introduction of a method to properly initiate the fracture into a specific direction using super-high-energy jetting. A drawback of this jetting method though is not knowing exactly where the far-field fracture has gone. Although we know that the fracture will extend in the local minimum-stress direction, it is not known where that direction might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It has been shown that redirection of fractures so that they extend into the highly permeable areas is possible (Surjaatmadja 2007a(Surjaatmadja , 2007b(Surjaatmadja , and 2007cSurjaatmadja 2008). In this work, a second fracture was placed after a short time delay after the placement of the first fracture and it was believed and shown that the second fracture could extend perpendicularly from the previous fractures.…”
Section: The Art Of Fracture-direction Modificationmentioning
confidence: 80%
“…It has been shown that redirection of fractures so that they extend into the highly permeable areas is possible (Surjaatmadja 2007a(Surjaatmadja , 2007b(Surjaatmadja , and 2007cSurjaatmadja 2008). In this work, a second fracture was placed after a short time delay after the placement of the first fracture and it was believed and shown that the second fracture could extend perpendicularly from the previous fractures.…”
Section: The Art Of Fracture-direction Modificationmentioning
confidence: 80%
“…Using this type of system, windows can be opened or closed in any sequence as prescribed. The process takes advantage of two phenomena: the altered stresses that can occur when a nearby fracture is opened (Warpinski et al 1989, Surjaatmadja 2007a, 2007b, 2007c2008;Moschovidis et al 2000) and the creation of slip planes by the naturally varying widths of each fracture forming the horizontal microfractures, as illustrated in Fig. 7 (Surjaatmadja 2010).…”
Section: Asf Methodsmentioning
confidence: 99%
“…As such, formations were generally near the surface. It was quite common for hydrocarbons to be discovered at depths less than 4,000 ft, and performing simple fracture stimulations was usually sufficient to obtain acceptable production (Surjaatmadja 2007a(Surjaatmadja , 2007b(Surjaatmadja , 2007c(Surjaatmadja , 2008(Surjaatmadja , 2010Lewis and Surjaatmadja 2015). However, as shallow formations became less productive and deeper formations were explored, finding new producing areas in a known producing formation could be described as Љhit and missЉ (Surjaatmadja et al 2003), meaning that luck was often a factor.…”
Section: Modifying the Direction Of Maximum Stressmentioning
confidence: 99%
“…Surjaatmadja suggests that the missing factor in these studies was time (Surjaatmadja 2007a(Surjaatmadja , 2007b(Surjaatmadja , 2007c(Surjaatmadja , 2008) (e.g., the dynamics of the rock movement process). He argues that the behavior of formation rock can be conveniently modeled as a Couette interaction between rock layers (or, in Couette's terms, Љflow linesЉ); hence, the behavior of the rock during a fracture opening process can be represented by a very viscous media, such as plastic models.…”
Section: Introductionmentioning
confidence: 97%